MENINGKATKAN PROFESIONALISME GURU DALAM MELAKSANAKAN PEMBELAJARAN FISIKA MELALUI BIMBINGAN TEKNIK KERJA KELOMPOK - Penjelasan . (Jurnal Pendidikan Fisika, 2013)
The objective in this research is to improve the professionalism ofteachers in implementing the guidance of physics learning through groupwork techniques in Sub Rayon 05 SMA Negeri 1 Percut Sei Tuan. Thesubjects were high school physics teachers are included in Sub Rayon 05 SMA Negeri 1 Percut Sei Tuan, amounting to 15 people. The research methodapplied is Action Research School through two cycles, with each cycleconsisting of planning, implementation, observation and reflection. Results ofdata analysis showed that (1) through the application of technical guidance tothe group work of teachers in the Physics Sub Rayon 05 SMA Negeri 1 Percut Sei Tuan, their knowledge of the methods, strategies, models and learningapproach that includes the model of physics learning experience improvement.(2) There is an increase in the ability of physics teachers in Sub Rayon 05SMA Negeri 1 Percut Sei Tuan in implementing models learning toimplement technical guidance group work. (3) Through the implementation oftechnical assistance work group, an increase in the ability of physics teachersin Sub Rayon 05 SMA Negeri 1 Percut Sei Tuan in preparing lesson plan inaccordance with the model or learning strategies. (4) There is an increase inthe ability of physics teachers in Sub Rayon 05 SMA Negeri 1 Percut SeiTuan in making the assessment instrument.